Analysis of Halophilic Phenotypic Variation and Cytotoxicity of Vibrio parahaemolyticus from Different Sources - Jingyue Gu; Xin Dong; Yunqian Zhou; Ying Zhao; Qiang Du; Jia Chen; Xujian Mao; Fengming Wang; Bowen Tu (Pathogens)
Vibrio parahaemolyticus is an aquatic animal pathogen. Recently, the detection rate of V. parahaemolyticus in freshwater products has exceeded that in seafood products, and the strains isolated from freshwater products exhibit better growth conditions in low-salinity environments. This study is based on a food risk detection activity in Changzhou, Jiangsu Province, China, investigating the variation of halophilism and the virulence of two groups of strains under different salt concentrations. Under 0%, 0.5%, and 1% salt, the strains from the freshwater showed faster growth than those from the seawater. In comparison, the strains from the seawater group under 2% and 3% salt grew faster than the growing status under the foregoing low-salt concentration environment. The cytotoxicity produced by the two strains was approximately 1.4 times higher in the 0.5% and 1% salt concentration groups compared to the 3% corresponding experimental group. Under the 0%, 0.5%, and 1% salt, the cytotoxicity of strains in the freshwater group increased by nearly 20% compared to that in the seawater groups. The freshwater strains showed altered halophilism and adapted to the low-salt environment. This research will be helpful in establishing a local and global control strategy against the diseases resulting from V. parahaemolyticus.